One child in 33 is a twin or higher multiple - using the LSAC data to identify the needs of multiple birth families - Hay, D (My University, 2007)
This presentation highlights some of the problems facing twins and multiple birth siblings and their families, which will be able to be analysed within 'Growing Up in Australia, the Longitudinal Study of Australian Children' (LSAC). The author outlines the rise in the rate of multiple births in the last few decades, the high risk rates of congenital disorders and speech and reading problems, low birth weights, the high risk rates of postnatal depression by mothers and child abuse, and increased pregnancy and child rearing costs.
Keywords: Families; Families and relationships; Families; Families and relationships